Hip joint mechanics in patients with osteonecrosis of the femoral head following treatment by advanced core decompression. (April 2022) - Tran, Thanh Ngoc; Wolf, Milan; Winter, Philipp; Landgraeber, Stefan
Abstract: Background: Osteonecrosis of the femoral head is a serious disease which, if left untreated, leads to destruction of the affected hip joint. For treatment of early stages of this disease, core decompression is the most common procedure. This study investigated the influence of the necrotic lesion and core decompression on the stress pattern in the hip joint using finite element analysis. Methods: Subject-specific models were generated from CT scan data of 5 intact hips. For each intact hip, twelve affected hip models were created by imposing a necrotic lesion in the femoral head, and four treated models were then created from four affected ones with central lesion, respectively. Treated models were created by supposing that the defect zone and the drill canal were filled with a bone substitute. Totally 105 hip models from three groups (intact, affected and treated) were simulated during normal walking activity. Findings: Necrotic lesion modified the stress distribution within the femoral head. Peak stress increased significantly up to 186% in mean in hips with a large lesion indicating an increased risk of femoral head collapse. Additionally, the presence of a medium to large necrosis altered significantly stress values ( P < 0.05) and pattern in the articular cartilage. Our study revealed that advanced core decompression can recover normal cartilage stress values and pattern in treated joint. Interpretation: The presence of a large lesion increased the risk of femoral head collapse. Advanced core decompression with bone grafts can restore normal cartilage mechanics in hip postoperatively. Highlights: The presence of a large necrotic lesion increases the risk of femoral head collapse. The presence of a medium to large lesion indicates a high risk of articular cartilage degeneration. Advanced core decompression with bone grafts can restore normal cartilage mechanics in hip.